2022
DOI: 10.3390/ijerph19148452
|View full text |Cite
|
Sign up to set email alerts
|

Post-Traumatic Stress Disorder Trajectories the Year after COVID-19 Hospitalization

Abstract: Background: Coronavirus disease (COVID-19) hospitalization has been related to Post-Traumatic Stress Disorder (PTSD). Available information is limited by insufficient follow-up and lack of longitudinal studies. Baseline factors (e.g., sex; obesity) have been related to PTSD, but post-hospitalization factors have not been studied. Objective: This study aimed to analyse prevalence, baseline, post-discharge factors and possible clinical courses of PTSD after hospitalization for COVID-19. Method: 109 patients (94.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 43 publications
2
9
0
2
Order By: Relevance
“…In accordance with the previous studies on PTSD in patients with COVID-19 and critical diseases [ 19 , 23 , 25 ], there exist four different courses of PTSD after COVID-19. The majority of patients (75%) were “resilient,” with no clinically relevant PTSD symptoms at all time points, and 10% of the patients were “recovery,” with a decrease in PTSD symptoms.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…In accordance with the previous studies on PTSD in patients with COVID-19 and critical diseases [ 19 , 23 , 25 ], there exist four different courses of PTSD after COVID-19. The majority of patients (75%) were “resilient,” with no clinically relevant PTSD symptoms at all time points, and 10% of the patients were “recovery,” with a decrease in PTSD symptoms.…”
Section: Discussionsupporting
confidence: 88%
“…In the sample, 49 patients (68.1%) were men. The median length of hospital stay was 13.0 days (IQR [ 8 , 25 ]), and 21 participants were classified into the severity scale 3, 34 to the severity scale 4, five to severity scale 5, and 12 to severity scale 6 or 7.
Figure 1 Patient flow IES-R, Impact of event-scale revised.
…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have shown that patients affected by COVID-19 should be considered as at risk patients for developing PTSD, and some authors have requested a specific survey for these patients to detect the occurrence of posttraumatic symptoms as early as possible [ 47 ]. We did not find these results for the presumptive diagnosis of PTSD assessed by PCL-5.…”
Section: Discussionmentioning
confidence: 99%
“…Mazza et al found a significant increasing trend of depression and anxiety in Covid-19 survivors 6 and 12 months after recovery (Mazza et al, 2022 ). Serra et al reported a 23.9% PTSD prevalence in Covid-19 survivors one year after hospitalization (Serra et al, 2022 ). Therefore, all these findings confirm the high probability of mental disorders in the survivors of Covid-19 over time.…”
Section: Discussionmentioning
confidence: 99%